Diseño de una planta desalinizadora de agua de mar basada en la tecnología de osmosis inversa para abastecer de agua potable a las comunidades indígenas de la Alta Guajira (2021)
The population of the Colombian Alta Guajira is considered a poor population within the Colombian Caribbean Coast, with a poverty value of 96%. Among the substantial difficulties these communities face is a deficient supply of drinking water, which the government has neglected for a long time. To find a possible solution to this problem, this project proposes the design of a desalination plant using the principle of reverse osmosis, as a way for communities to extract the valuable resource from the seas and nearby water accesses. Research is denoted as an applied project, under a quantitative approach. The results do not constitute a solution for the problem, rather they clearly express how this problem can be approached from the research